Protective role of host complement system in Aspergillus fumigatus infection - Shende, Rajashri; Wong, Sarah Sze Wah; Meitei, Heikrujam Thoihen; Lal, Girdhari; Madan, Taruna; Aimanianda, Vishukumar; Pal, Jayanta Kumar; Sahu, Arvind (Frontiers in Immunology, 2022)
Invasive aspergillosis (IA) is a life-threatening fungal infection for immunocompromised hosts. It is, therefore, necessary to understand the immune pathways that control this infection. Although the primary infection site is the lungs, aspergillosis can disseminate to other organs through unknown mechanisms. Herein we have examined the in vivo role of various complement pathways as well as the complement receptors C3aR and C5aR1 during experimental systemic infection by Aspergillus fumigatus, the main species responsible for IA. We show that C3 knockout (C3-/-) mice are highly susceptible to systemic infection of A. fumigatus. Intriguingly, C4-/- and factor B (FB)-/- mice showed susceptibility similar to the wild-type mice, suggesting that either the complement pathways display functional redundancy during infection (i.e., one pathway compensates for the loss of the other), or complement is activated non-canonically by A. fumigatus protease. Our in vitro study substantiate the presence of C3 and C5 cleaving proteases in A. fumigatus. Examination of the importance of the terminal complement pathway employing C5-/- and C5aR1-/- mice reveals that it plays a vital role in the clearance of conidia. This, in part, is due to the increased conidial uptake by phagocytes. Together, our data suggest that the complement deficiency enhances the susceptibility to systemic infection by A. fumigatus.